Three Oriental species of Pseudoaerumnosa Rudzinski (Diptera, Sciaridae) from China - Chen, Zuluan; Yang, Xue; Menzel, Frank; Wu, Hong; Huang, Junhao (Zootaxa, 2021)
Three Oriental species of the genus Pseudoaerumnosa Rudzinski, 2006 from China are described and illustrated: P. regularis sp. n., P. tianmushana sp. n. and P. tkoci Vilkamaa, Halenius & Ševčík, 2019. The morphological species concepts were supported by the DNA barcodes of COI sequences. The genetic distances of Pseudoaerumnosa species were analyzed and a neighbor-joining tree was constructed, based on 37 sequences of nine species.